Development of a Novel Three‐step Sonogashira Cross Coupling/Deacetonation/Cycloaddition Protocol for the Synthesis of 4‐aryl‐1, 2, 3‐triazoles Using 2‐methyl‐3‐butyn‐2‐ol as a Versatile Acetylene Surrogate. Issue 5 (30th March 2021) - da Silva, Everton M.; de Albuquerque, Danilo Yano; Zukerman‐Schpector, Julio; Schwab, Ricardo S.
Abstract: A practical, and efficient microwave‐assisted, three‐step Sonogashira cross‐coupling/Deacetonation/Cycloaddition sequence has been developed for the synthesis of a variety of 4‐aryl‐1, 2, 3‐triazoles from readily available starting materials. The important features of this synthetic sequence include the use of inexpensive 2‐methyl‐3‐butyn‐2‐ol as an acetylene surrogate, 2‐Me‐THF as a bio‐based solvent, short reaction time, good yields, avoiding the isolation of volatile terminal alkynes. Abstract : This work presents a novel and simple route to synthesize 4‐aryl‐1, 2, 3‐triazole by the three‐step Sonogashira cross coupling/Deacetonation/Cycloaddition three‐step sequence under microwave irradiation. Furthermore, the protocol proceeds under mild conditions starting from 2‐methyl‐3‐butyn‐2‐ol as an acetylene surrogate in the presence of bio‐based solvent 2‐Me‐THF.